Edukasi Pencegahan Anemia Remaja Putri pada Masa New Normal COVID-19 di SMK Panca Atma Jaya Klungkung - Kadek Primadewi; Ni Putu Diwyami; Made Rai Mahardika (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2021)
Background: Anemia is a condition in which the concentration of hemoglobin (Hb) in the blood is lower than the normal value. Anemia that occurs due to iron deficiency so that the formation of red blood cells and other functions in the body is disrupted is iron nutritional anemia. Based on Riskesdas data in 2018, the prevalence of anemia was 48.9% in the 15-24 year age group. According to WHO, adolescents are residents in the age range of 10-19 years, young women have a higher risk, this is because young women experience menstruation (menstruation) every month. The impact of the incidence of anemia in adolescents can reduce concentration and learning achievement, as well as affect productivity among youth. Based on this background, the author is interested in carrying out community service activities for the prevention of anemia in young women during the new normal period of Covid-19 at Panca Atma Jaya Vocational School, Klungkung. Purpose: The purpose of this activity is as a form of implementation of Tri Dharma Stikes Panca Atma Jaya Klungkung. Methods: Participants who took part in this activity were 67 students using the pretest and posttest methods. Results: The results obtained were an increase in the pretest score (before being given education) which was 69.41% to 89.42% in the posttest result (after being given education). Conclusion: There is a significant relationship between posttest scores, which increases after education is held, so anemia prevention education needs to be given and improved to improve anemia prevention behavior in adolescent girls.